Health promotion method of small group discussion effectively increases the behaviour of mosquito eradication in Gunungkidul Yogyakarta - Sujono Riyadi; Ferianto Ferianto (Alma Ata University Press, 2021)
Background: In Indonesia, Dengue Hemorrhagic Fever (DHF) is a disease that is a public health problem, many areas have become endemic. This disease has become a global health problem. This disease is a recurring disease, so it needs serious handling. Objectives: The purpose of this study was to determine the effectiveness of the lecture method and small group discussions on community behavior in eradicating mosquitoes. Methods: This research is a survey method in the form of a quantitative design with a quasi-experimental type. The technique used is a time series control with a sample size of 400 people carried out in Gunungkidul Yogyakarta Regency in May-July 2020. A total of 200 subjects were given health promotion interventions with the lecture method, and 200 other subjects were given health promotion using the small group discussion method. Before being given the Health promotion, every resident's house was checked for the presence of larvae, and after being given the Health promotion, the presence of larvae was re-checked for three weeks. The data obtained were analyzed using the Mann-Whitney test using the SPSS program.Results: This research shows an effect of giving health promotion with lecture method or small group discussion method on community behaviour changes in eradicating mosquito nests with p-value <0.001. Conclussion: Health promotion using the small group discussion method is more effective than Health promotion using the lecture method. Health promotion using the small group discussion method effectively changes people's behaviour to eradicate mosquito nests.